Islamic Character Formation through School-Based Habituation: The Roles of Islamic Education Teachers and the Family Environment - Wulan Sari; Yanuardin (Yayasan Bayt Shufiya Nusantara, 2026)
Islamic character education in Indonesian public senior high schools faces a recurring tension between students’ participation in school-organized religious rituals and the consistency with which ethical and religious values are enacted in everyday life. This qualitative case study examines the dynamics of Islamic character habituation at SMA Negeri 1 Galang, Deli Serdang, North Sumatra, by integrating three dimensions that are often analyzed separately: the pedagogical strategies of Islamic Religious Education (IRE) teachers, school discipline and religious-culture policies, and the continuity of reinforcement in the family environment. Data were generated through observation, interviews, and document analysis and were analyzed iteratively through data reduction, display, conclusion drawing, and verification, with source and technique triangulation. The findings identify a central analytic category termed habituation discontinuity, defined as the weakening or interruption of school-cultivated religious routines and ethical expectations when students move into home and peer contexts in which those practices are not consistently reinforced. Within the school, character formation was supported by teacher modeling, recurrent disciplinary and religious practices, the Pencerahan Kalbu reflective forum, the Islamic Spirituality Student Organization (Rohis), and adaptive use of digital media. However, ritual participation functioned primarily as a behavioral indicator and could not, by itself, demonstrate moral internalization. The case also showed tensions in dress ethics and Qur’anic literacy that pointed to uneven internalization of religious values. The study contributes an integrative school–family perspective to research on Islamic character education and suggests that sustainable character formation requires a shift from institutionally controlled compliance toward coordinated pedagogical reinforcement across school, family, and community settings.